DOES PERCEIVED VALUE ACCOMPANIED BY SATISFACTION INFLUENCE GOJEK'S CUSTOMER LOYALTY? - Muhammad Roy Aziz Haryana (UNIB Press, 2024)
Technological advancements in business have significantly transformed the domains of business operations and finance, particularly in the context of customer loyalty towards online transportation services such as Gojek. This study addresses the challenges faced by customer loyalty amidst intense business competition and underscores the necessity for business processes to remain uninterrupted regardless of external conditions. The primary objective of this research is to investigate the determinants of customer loyalty, focusing specifically on value perception and customer satisfaction. Building upon the research conducted by Diallo, Diop-Sall, Djelassi, and Godefroit-Winkel (2018), which highlighted the influence of perceived benefits and positive experiences on customer loyalty, this study extends the theoretical framework to examine the interplay between value perception and customer satisfaction in the context of Gojek. Methodologically, the study employed a sample of 100 respondents and utilized Partial Least Squares (PLS) for hypothesis testing. The findings reveal that both value perception and satisfaction have a significant impact on customer loyalty towards Gojek in Yogyakarta. This study illustrates that Gojek's customer loyalty in Yogyakarta remains robust despite the prevailing competitive pressures. Consequently, it is imperative for Gojek’s management to continuously nurture and enhance customer loyalty irrespective of competitive challenges. Furthermore, the research contributes valuable insights for scholars in the fields of business and finance, particularly in the realm of customer loyalty research